Unveiling Fahr’s Syndrome in a Young Female: A Case of Seizures and Metabolic Imbalance That Challenges Established Diagnostic Criteria - Syed Hammad Ali (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction: Fahr’s syndrome is a rare neurological disorder characterized by idiopathic basal ganglia calcification, often associated with metabolic disturbances like hypoparathyroidism. This report presents the case of a 14-year-old female who exhibited a combination of neurological symptoms and metabolic abnormalities. Methods: A 14-year-old female presented with fever, productive cough, and subsequent generalized tonic-clonic seizures. Initial empirical treatment included sodium valproate, ceftriaxone, vancomycin, and dexamethasone. Investigations included cerebrospinal fluid (CSF) analysis, CT brain scan, EEG, and serum electrolyte measurements. Results: The patient’s CT scan revealed extensive bilateral symmetrical calcifications in the basal ganglia, periventricular deep white matter, and cerebellar hemispheres, indicative of Fahr’s syndrome. Laboratory tests confirmed hypoparathyroidism, with hypocalcemia, hypomagnesemia, and hyperphosphatemia. The treatment regimen was adjusted to include intravenous calcium gluconate, vitamin D, and magnesium sulphate. Upon discharge, the patient was asymptomatic, and a follow-up two weeks later showed improved serum calcium levels and no recurrence of symptoms. Conclusion: This case underscores the necessity of considering Fahr’s syndrome in the differential diagnoses of seizures with metabolic disturbances. Timely diagnosis and appropriate management of the underlying metabolic abnormalities can result in significant clinical improvement and prevent recurrence of symptoms. It also nullifies previous diagnostic criteria, raising new gaps to be explored.